2005
DOI: 10.1271/bbb.69.224
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Apoptosis Induced by Fucoxanthin in Human Promyelocytic Leukemia Cells

Abstract: Apoptosis induced by fucoxanthin in HL-60 cells was associated with a loss of mitochondrial membrane potential at an early stage, but not with an increase in reactive oxygen species. Fucoxanthin treatment caused cleavages of procaspase-3 and poly (ADP-ribose) polymerase without any effect on the protein level of Bcl-2, Bcl-X L , or Bax. Apoptosis induction by fucoxanthin may be mediated via mitochondrial membrane permeabilization and caspase-3 activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 8 publications
1
60
1
1
Order By: Relevance
“…Kotake-Nara et al reported that fucoxanthin (20 μM) induced DNA fragmentation as indicated by a TdT-mediated dUTP nick end labeling method using human prostate cancer cells PC-3, DU145 and LNCap cells (21). Furthermore, they observed that fucoxanthin (10 μM) induced caspase-dependent apoptosis in human promyelocytic leukemia HL-60 cells via loss of mitochondrial membrane potential (22). Another study of theirs showed that fucoxanthin (20 μM) induced caspasedependent apoptosis accompanied by a decrease in BCL2-associated X (BAX) and BCL2 protein levels in PC-3 cells (23).…”
Section: Fucoxanthin Inhibits Tumor Cell Growth By Inducing G 1 Cell-mentioning
confidence: 99%
“…Kotake-Nara et al reported that fucoxanthin (20 μM) induced DNA fragmentation as indicated by a TdT-mediated dUTP nick end labeling method using human prostate cancer cells PC-3, DU145 and LNCap cells (21). Furthermore, they observed that fucoxanthin (10 μM) induced caspase-dependent apoptosis in human promyelocytic leukemia HL-60 cells via loss of mitochondrial membrane potential (22). Another study of theirs showed that fucoxanthin (20 μM) induced caspasedependent apoptosis accompanied by a decrease in BCL2-associated X (BAX) and BCL2 protein levels in PC-3 cells (23).…”
Section: Fucoxanthin Inhibits Tumor Cell Growth By Inducing G 1 Cell-mentioning
confidence: 99%
“…In other words, CCl 4 -induced hepatocyte apoptosis was apparently prevented by pretreatment with fucoxanthin, suggesting that fucoxanthin has an anti-apoptotic effect and inhibited the toxic damage. There have been a number of reports on the anticancer properties of fucoxanthin through apoptosis induction (Hosokawa et al, 2004;Kotake-Nara et al, 2005;Yu et al, 2011), while the anti-apoptotic effect of fucoxanthin was reported in only a single in vitro study (Heo and Jeon, 2009). This is the first study to demonstrate the antiapoptotic effect of fucoxanthin in vivo.…”
Section: Discussionmentioning
confidence: 83%
“…Fucoxanthin is a marine carotenoid found in wakame (undaria pinnatifida) and Hijiki (Hijikia fusiformis) and has certain remarkable biological properties, including antioxidant activity (Miyashita, 2009;Kim et al, 2010), an anti-inflammatory effect (Sakai et al, 2009), an anti-carcinogenic effect (Hosokawa et al, 2004;Kotake-Nara et al, 2005;Yu et al, 2011) and even utility as an anti-obesity agent (Maeda et al, 2005;Abidov et al, 2010). The major structural difference between fucoxanthin and the other carotenoids is the presence of an unusual allenic bond, and this bond was shown to be responsible for the higher antioxidant activity of fucoxanthin (Dembitsky and Maoka, 2007;Sachindra et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Edible brown algae are the best sources of Fx (Kim and Pangestuti, 2011;Peng et al, 2011). In recent years, interest has focused on the functional benefits of Fx, with the discovery of antioxidative (Sachindra et al, 2007), anticancer (Kotake-Nara et al, 2005;Sugawara et al, 2006) and antiobesity (Maeda et al, 2005) effects. Among the functions of Fx, antiobesity effects have been well established.…”
Section: Introductionmentioning
confidence: 99%